ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KABUPATEN SIMEULUE - Yoyon Safrianto (JURNAL EKOMBIS, 2018)
This report aims to understand sector affecting economic growth in simeulue district, in the period 2008-2017.But the data collected is the data on economic growth, government investment and labor sourced from statistics ( BPS ), the financial management and local asset ( DPKKD ) and social affairs, labor and transmigration department.Model analysis the data used was linear regression multiple, correlation analysis and testing hypothesis t use test and the f. Based on multiple linear regression results interpretation with the equation LnY = α + β1LnX1 + β1 LnX2 + e, we can see the size of the contribution variable free on variables bound namely investment (0,074) and 1,128 ) of labor , it means variable free X (investment and of labor) can increase economic growth in kabupaten simeulue .The value of R (correlation coefficient) as much as 0,891 , means that the value the correlation is very strong show of closeness as it had remained in hose 0.8-1. Between X1 (government investment) with (economic growth) show tstat<ttable is 1,046< 1,895.While between X2(of labor) with Y (economic growth) shows tstat>ttable is 4,541> 1,895. In the F (13,472 > 3,79) significant to the level of errors a = 5percent. This means H0 in good and H1 accepted, it means investment and labor simultaneously significant on economic growth in the Simeulue.Recommendations, regional growth can continue to increase in with penigkatan skill labor and optimization the economic growth has increased from sector-sector (GDP) another.Keywords: Economic growth, Investment and Labor